2013
DOI: 10.1371/journal.pone.0073301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori Biofilm Formation on Clarithromycin Susceptibility and Generation of Resistance Mutations

Abstract: The human gastric pathogen Helicobacter pylori forms biofilms in vitro and in vivo. The purpose of this study was to evaluate the effects of H. pylori biofilm formation in vitro on clarithromycin (CLR) susceptibility. CLR susceptibility of H. pylori intermediate (2-day) and mature (3-day) biofilms on glass coverslips was determined at concentrations from 0.03 to 0.5 µg/ml. H. pylori biofilm biomass was increased after treatment with CLR at minimum inhibitory concentration levels by up to 4-fold (2-day biofilm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 46 publications
3
67
0
6
Order By: Relevance
“…However, the impact of biofilm mode of growth on susceptibility to antimicrobial agents in H. pylori has not been well documented. Previous studies have shown that H. pylori clinical strains TK1402 and TK1049 increased levels of tolerance and resistance to clarithromycin of up to 8 to 16-fold times the minimum inhibitory concentration (MIC) as compared to planktonic grown cells (Yonezawa, Osaki et al 2013, Yonezawa, Osaki et al 2019. We thus decided to investigate this phenomenon in the strong-biofilm forming strain G27 and determine biofilm and planktonic cells susceptibility to three clinically relevant antibiotics: the macrolide clarithromycin, the b-lactam amoxicillin, and tetracycline.…”
Section: Biofilm Cells Demonstrate High Levels Of Antibiotic Tolerancmentioning
confidence: 98%
“…However, the impact of biofilm mode of growth on susceptibility to antimicrobial agents in H. pylori has not been well documented. Previous studies have shown that H. pylori clinical strains TK1402 and TK1049 increased levels of tolerance and resistance to clarithromycin of up to 8 to 16-fold times the minimum inhibitory concentration (MIC) as compared to planktonic grown cells (Yonezawa, Osaki et al 2013, Yonezawa, Osaki et al 2019. We thus decided to investigate this phenomenon in the strong-biofilm forming strain G27 and determine biofilm and planktonic cells susceptibility to three clinically relevant antibiotics: the macrolide clarithromycin, the b-lactam amoxicillin, and tetracycline.…”
Section: Biofilm Cells Demonstrate High Levels Of Antibiotic Tolerancmentioning
confidence: 98%
“…Biofilm formation by H. pylori has been demonstrated both in vitro (30)(31)(32) and in vivo (33)(34)(35)(36)(37). While it is unclear exactly what drives biofilm formation in H. pylori, protection from antibiotics and host defenses during infection (35,38,39) and/or protection in putative environmental reservoir (40-43) have been proposed. Basic characterization has shown that in vitro biofilm formation is varied across strains (32) and appears to be induced under conditions, such as serum/nutrient starvation (44,45).…”
mentioning
confidence: 99%
“…These results correlate with the findings from other studies in which the H. pylori biofilm was treated with MIC of clarithromycin. A 4-fold and 16-fold increase in biofilm biomass was observed in 2-day and 3-day culture, respectively (21). For the three antibiotics most commonly used for eradication of this pathogen, i.e.…”
Section: H Pylori Morphological Formsmentioning
confidence: 90%